THE EFFECT OF PROBLEM BASED LEARNING ON ENVIRONMENTAL CARE ATTITUDES AND LEARNING OUTCOMES - Amin, Saiful; Bashith, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This study aims to 1) determine the effect of problem-based learning on environmental care attitudes and 2) determine the effect of problem-based learning on learning outcomes. This research is a quasi-experimental with control group pretest-posttest design. The research subjects were students of the Social Sciences Education Department, UIN Maulana Malik Ibrahim Malang. Research data were analyzed by t-test technique at a significance level of 5%. The results showed that 1) problem-based learning effects on the environmental care attitude of Social Studies Education students, UIN Maulana Malik Ibrahim Malang and 2) problem-based learning affects the learning outcomes of social studies education students, UIN Maulana Malik Ibrahim Malang.